Comparison of Conventional and Molecular techniques with inflammatory markers in differentiation of bacterial and non-bacterial Cholecystitis - Maysaa Saleh Mahdi; Ali Abdul kadhim jasim (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background/aims: The presence of bacteria in bile during surgery or invasive diagnostic procedures predisposes to septic complications.Traditional methods in identifying bacterial agents aretime-consumingand some bacteria are difficult to grow or even non-cultivable. This study aims to compare molecular methods and inflammatory indices with conventional culture method in identification of infection in patients with cholecystitis. Methods:Across-sectional study was conducted. Twenty-nine bile fluids along with blood samples were taken from patients who underwent laparoscopic cholecystectomy. Bile samples were used for both culture and deep sequencing of bacterial 16S rRNA. blood was used to detect C-reactive protein and Complete blood count. Results:From Twenty-nine patients with cholecystitis, Culturing of Bile identified only 6 (20.7%) positive for bacterial growth whereas sequencing revealed 27(93.1%). Serum inflammatory markers CRP, WBC, NLR, PLR and SII levels were higher in patients infected with pathogenic bacteria. ROC curve analysis showed that PLRhad the highest discriminatory power (AUC=0.75). Conclusion: Molecular method was better than conventional culture technique in identifying the presence of bacterial infection. Inflammatory markers had acceptable power in discrimination between infection with pathogenic and non-pathogenic bacteria.